Higher Peripheral Cholesterol and a Positive Correlation With Risk for Large-For-Gestational-Age Neonates in Pre-Pregnancy Underweight Women - Wang, Dongyu; Ding, Wenjing; Ding, Chengcheng; Chen, Haitian; Zhao, Weihua; Sun, Bo; Wang, Zilian (Frontiers in Endocrinology, 2021)
Objective: As the high proportion of underweight pregnant women, omission of their weight gain and blood lipids management during gestation might lead to adverse pregnancy outcomes. This study aimed to determine the relationship between lipid profile and risks for adverse pregnancy outcomes in pre-pregnancy underweight women. Methods: This study was part of an ongoing cohort study including Chinese gravidas delivered from January 2015 to December 2016. Included subjects were grouped into underweight, normal-weight, and overweight by BMI before conception. Logistic regression was used to assess the association between lipid profiles during second trimester and adverse obstetric outcomes in each group. A subgroup analysis according to the gestational weight gain, in which subjects in each group were divided into above and within the Institute of Medicine (IOM) recommendations, was performed. Results: A total of 6, 223 women were included. The proportion of underweight (19.3%) was similar to that of overweight women (19.4%) in South China. Peripheral total cholesterol (TC) level in underweight women was significantly higher than that in overweight women (P <0.001). After adjusting maternal age, TC level was positively correlated to the risk for large-for-gestational-age (LGA) [aOR =2.24, 95%CI (1.08, 4.63)], and negatively related to the risk for small-for-gestational age (SGA) [aOR =0.71, 95%CI (0.59, 0.85)] in underweight women, but not in normal-weight or overweight women. The subgroup analysis showed that maternal TC level was positively correlated with the risk of LGA only in underweight women who gained weight more than the IOM recommendations. Conclusion: Underweight pregnant women with high TC levels had a higher risk for LGA, especially among women whose gestational weight gain were above the IOM recommendations. Therefore, clinical management of lipids and weight gain during gestation should also be recommended for underweight women.